Application Status and Challenge of PROFIBUS Technology in Industrial Automation Field - Zhe, Qiang; Sun, Hongxiao; Liu, Yuliang; Rao, Ziyi; Liang, Geng (International Journal of Mechanical and Electrical Engineering, 2024)
This article first introduces the basic concepts and principles of PROFIBUS technology, and then elaborates on its application status in the field of industrial automation from three aspects: manufacturing, process control, and drive technology, including its wide range of applications and advantages. Subsequently, the main challenges currently faced by PROFIBUS technology were analyzed, such as integration with emerging industrial Ethernet technologies, data security issues, and the complexity of system upgrades and maintenance. Finally, the article looks forward to the future development trends of PROFIBUS technology, including further integration with industrial Ethernet technology and the introduction of encryption algorithms to enhance data security. Overall, PROFIBUS is a mature fieldbus technology. Still crucial in the field of industrial automation. However, with the development of new technologies and changes in application requirements, its future development still faces many challenges and opportunities.